A wideband frequency reconfigurable antenna with improved gain. Issue 3 (16th December 2022) - Sheng, Lili; Meng, Liang; Lin, Yixiang; Gong, Yanping; Yang, Xiaohui; Cao, Weiping
Abstract: A wideband frequency reconfigurable antenna based on active artificial magnetic conductor (AAMC) surface is proposed with improved gain. The AAMC element consists of a composite polygon‐rectangle‐ring with five patches and a cross‐strip inside. A reverse‐bias varactor is inserted between the ring and ground plane to make the in‐phase reflection frequency bands adjustable. A dipole is placed above the AAMC surface which is composed of 5 × 5 unit cells. The measured results show that the reconfigurable frequency ranges from 1.64 to 4.16 GHz while maintaining the radiation patterns stable. Moreover, the peak gain reaches 10.65 dBi at 3.5 GHz.